Analisis Kinerja Sistem Kripto kompresi Pada File Dokumen Dengan Algoritma Asimetris RSA dan Even Rodeh Code - Imam Prayoghi; Imran Lubis; Haida Dafitri (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
The document files are electronic data that are often used to store information that is personal or confidential, therefore it is necessary to take action to keep the information accessible only to the owner of the data. In addition to the security aspect, the thing that needs to be considered is also about storage memory. Therefore, additional steps are needed to streamline the storage media and speed up the transmission process by compressing it first so that its size becomes smaller. In this study, will combine cryptography and compression techniques using the RSA algorithm for the purpose of securing data, then compressed using the Even Rodeh Code algorithm to reduce the size of the data. This research produces an application that can be used as an alternative solution in maintaining the confidentiality of document file data so that it can only be accessed by the data owner and can save the need for data storage space to be more efficient. The test results show that different test file sizes produce different Compression Ratio (CR), Space Savings (SS) and RT (Running Time) calculation values as well. The larger the size to be compressed, the larger the size that can be reduced or the greater the storage space that can be saved. While the RT results have increased in value constantly along with changes in the size of the test file used. This means that the larger the size of the test file to be compressed, the longer it will take to compress it